Fatigue, symptom burden, and health‐related quality of life in patients with myelodysplastic syndrome, aplastic anemia, and paroxysmal nocturnal hemoglobinuria - Carmen P. Escalante; Stephanie Chisolm; Juhee Song; Marsha Richardson; Ellen Salkeld; Etsuko Aoki; Guillermo Garcia‐Manero (Cancer Medicine, 2019)
Abstract Background Fatigue is distressing and affects quality of life (QoL) among patients with myelodysplastic syndrome (MDS), aplastic anemia (AA), and paroxysmal nocturnal hemoglobinuria (PNH). Limited data exist on the impact of fatigue, QoL, and related symptoms in these patients. Objective Prospectively assess fatigue (functional assessment of cancer therapy‐anemia [FACT‐An]); QoL (FACT‐An subscales); pain (brief pain inventory); and depression, anxiety, and stress (depression anxiety stress scale‐21) and strategies used to manage these symptoms in patients with MDS, AA, and PNH. Methods Surveys were administered via the AA and MDS International Foundation website and database from October 2014 through April 2015 in a cross‐sectional study. Results were summarized using descriptive statistics. Results Of 303 patients, 145 (48%) had MDS, 84 (28%) had AA, and 74 (24%) had PNH; 31 (10%) had >1 diagnosis. The mean age was 57 years, 200 (66%) were female, and 195 (92%) were white. The mean fatigue scores were 25 (range 1‐52) for the whole cohort, 28 for AA, 25 for MDS, and 24 for PNH (P = 0.117); these are all considered severe level. The mean QoL score was 68 (range 10‐104) for the whole cohort, 67 for AA, 69 for MDS, and 67 for PNH (P = 0.821). The ranges for stress were normal; pain and depression, mild; and anxiety, moderate. The most common management strategies perceived as helpful for fatigue in the past month were preserving energy, physical activity, and naps. Conclusions Many patients with MDS, AA, and PNH report severe fatigue. The helpfulness of fatigue management strategies may impact patients’ continued use; whether these strategies are beneficial and decrease fatigue levels needs more study.